MATROGINÁSTICA - Storck, Adriane M.; Oliveira, Ana P. M. d.; Perius, Andressa; Rambo, Andréia; Oliveira, Carine C. d.; Gerhart, Cristiane; Lunardi, Cristina M. F.; Muller, Daniele; Wegner, Dayane; Bourscheid, Deise J.; et al. (Salão do Conhecimento, 2013)
Resumo